Pengaruh Pelatihan Komunikasi terhadap Kompetensi Klinis Perawat dan Kepuasan Pasien di RS Pangkalpinang - Pakpahan, Sinta Wahyuni; Hendriana, H. Heris; Rinawati, Rinawati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This study aims to analyze the impact of communication training on nurses’ clinical competence and patient satisfaction at RS Pangkalpinang. Effective communication is a critical component in enhancing healthcare quality, particularly in nurse–patient interactions. A quantitative approach with a survey method was employed, involving 53 nurses who had completed structured communication training and 25 patients treated by those nurses. Data were analyzed using simple and multiple linear regression with SPSS version 26. The results showed a significant improvement in nurses’ clinical competence, with mean scores increasing from 72.4 (pre-test) to 85.7 (post-test), particularly in the domain of therapeutic communication. Patient satisfaction scores also increased from an average of 78.2 to 88.9 after the training intervention. Regression analysis revealed that communication training had a significant positive effect on nurses’ clinical competence (R² = 0.48; p < 0.001) and on patient satisfaction (R² = 0.41; p < 0.01). These findings suggest that structured communication training grounded in theoretical models such as Peplau’s Interpersonal Theory and the Calgary-Cambridge Guide can enhance professional competence and improve patient perceptions of care. The practical implication is that hospitals should integrate communication training into ongoing staff development programs and consider its replication in other healthcare settings to improve the overall quality of nursing services.